USE OF SOCIAL MEDIA IN ELECTION CAMPAIGNING (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article is devoted to the study of the effectiveness and impact of the use of social media in the context of election campaigning. The author considers various aspects of interaction between political candidates and voters through social media platforms. It analyzes the impact of online communications, the forms and content of campaign materials, and the ways in which voters are mobilized using digital technologies. The paper also assesses the effectiveness of tactics and strategies employed by candidates to increase their visibility and impact on audiences during the campaign period. The paper includes an analysis of current trends and examples of successful use of social media in political campaigning, which makes it relevant for political scientists, marketers and social activists.
Keywords: social media, election campaigning, communications, individualization, public pages, rejection of strict moderation, target group, electoral process, election campaign,